2009
DOI: 10.1111/j.1749-6632.2009.05050.x
|View full text |Cite
|
Sign up to set email alerts
|

A Re‐evaluation of the Mechanisms Leading to Dengue Hemorrhagic Fever

Abstract: Viremia is one of the features of dengue virus infection among the flaviviruses. Dengue virus infection results in a spectrum Key words: flavivirus; dengue virus; DHF; DSSDengue virus infection and dengue disease are recognized as a major public health issue internationally.1 Dengue virus infection is the most important mosquito borne human disease in terms of morbidity and mortality in urban tropical area. Climate changes, such as global warming and El Nino, poorly urbanization planning, an increase in intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 40 publications
0
49
0
1
Order By: Relevance
“…With evidence suggesting platelets can be infected by DENV and become activated [17,18,31], an ex vivo study was carried out to verify the DENV-infected platelets, which could be aggregated with monocytes directly. Platelets were purified and infected with DENV as previously described [8].…”
Section: Resultsmentioning
confidence: 99%
“…With evidence suggesting platelets can be infected by DENV and become activated [17,18,31], an ex vivo study was carried out to verify the DENV-infected platelets, which could be aggregated with monocytes directly. Platelets were purified and infected with DENV as previously described [8].…”
Section: Resultsmentioning
confidence: 99%
“…our in vitro results confirm DV-triggered IL-1b synthesis by platelets. Whether this is due to outside-in activation of intracellular signaling pathways and/or internalization of DV into platelets 46,47 requires further investigation. We also recognize that other factors including cytokines, antibodies, and coagulation factors may also contribute to platelet activation in dengue.…”
Section: Discussionmentioning
confidence: 99%
“…[107][108][109] It has been suggested that the degree of thrombocytopenia correlates with clinical severity and complement activation. 110 As a result of reduced platelet counts and increased complement activation there is increased vascular fragility and thus an increased risk of haemorrhage.…”
Section: Thrombocytopeniamentioning
confidence: 99%